Pengaruh Kepribadian Extraversion dan Neuroticism Terhadap Kecenderungan Tindakan Fraud Accounting - Nanda Putri; Nayang Helmayunita (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of extraversion personality and neuroticism on the tendency of accounting fraud. This research is an associative causality study with a quantitative approach. The number of sample members is determined through the slovin formula. The samples in this study were undergraduate Accounting students in 2018 at Padang State University, Andalas University, and Bung Hatta University on the condition that they had passed courses in business ethics and the accounting and auditing professions. The data collection method used a questionnaire distributed through google form. The data used in this study is primary data. The hypothesis in this study was tested using multiple linear regression analysis with IBM SPSS 25. The results showed that extraversion personality had a significant effect on the tendency of accounting fraud. Meanwhile, neuroticism has no effect on the tendency of accounting fraud.